2008
DOI: 10.1016/j.yexcr.2008.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cell migration and invasion are regulated by expression of variant integrin glycoforms

Abstract: The ST6Gal-I glycosyltransferase, which adds α2-6-linked sialic acids to glycoproteins, is overexpressed in colon adenocarcinoma, and enzyme activity is correlated with tumor cell invasiveness. Previously we reported that forced expression of oncogenic ras in HD3 colonocytes causes upregulation of ST6Gal-I, leading to increased α2-6 sialylation of β1 integrins. To determine whether ras-induced sialylation is involved in promoting the tumor cell phenotype, we used shRNA to downregulate ST6Gal-I in ras-expressor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 53 publications
2
66
1
Order By: Relevance
“…The expression levels of ST6GAL1 mRNA and enzyme activities are known to be particularly enhanced in metastatic tumors, which were promoted by the Ras oncogene (15,16). Consistently, in vitro cell culture studies have suggested that ST6GAL1 up-regulation contributes to cancer metastasis by regulating invasiveness and/or cell motility (18,54), as observed in this study. It is worth noting that the effects of GOLPH3-mediated sialylation on cell migration and cellular signaling could not be excluded from other target proteins, such as EGFR.…”
Section: Discussionsupporting
confidence: 90%
“…The expression levels of ST6GAL1 mRNA and enzyme activities are known to be particularly enhanced in metastatic tumors, which were promoted by the Ras oncogene (15,16). Consistently, in vitro cell culture studies have suggested that ST6GAL1 up-regulation contributes to cancer metastasis by regulating invasiveness and/or cell motility (18,54), as observed in this study. It is worth noting that the effects of GOLPH3-mediated sialylation on cell migration and cellular signaling could not be excluded from other target proteins, such as EGFR.…”
Section: Discussionsupporting
confidence: 90%
“…A pooled population of clones stably expressing shRNA was generated by puromycin selection. Down-regulation of ST6Gal-I expression was confirmed by Western blot (19). SW48 cells were purchased from ATCC.…”
Section: Methodsmentioning
confidence: 99%
“…ST6Gal-I is overexpressed in many types of human cancers, including colon (58 -62), breast (63), ovarian (64), gastric (65), oral (66), cervical (67), choriocarcinoma (68), leukemia (69), and brain tumors (70), and high expression positively correlates with tumor metastasis and poor prognosis (61,63,66). Furthermore, both in vitro cell culture and animal studies have implicated ST6Gal-I in regulating tumor cell invasiveness and differentiation state, as well as metastasis (71)(72)(73)(74)(75)(76)(77)(78)(79). Although mechanisms regulating ST6Gal-I expression have not been widely investigated, it is known that ST6Gal-I is up-regulated by oncogenic Ras (reviewed in Ref.…”
Section: St6gal-i-dependent Inhibition Of Galectin Function May Promomentioning
confidence: 99%